2022
DOI: 10.3390/microbiolres13030034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Nutritional Zinc Forms on the Proliferation of Beneficial Commensal Microorganisms

Abstract: This study compared the minimal inhibition concentrations (MICs) and their effects on the growth kinetics of seven different types of zinc (Zn) compounds and Na2EDTA in the case of three typical commensal beneficial microorganisms (Bacillus subtilis, Lactococcus lactis, and Saccharomyces cerevisiae). The seven Zn compounds included ZnSO4, four Zn–amino acid chelates, and two Zn–EDTA complexes. Both MICs and growth kinetic parameters indicated that different microorganisms show different sensitivities; for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Therefore, the search for new zinc (Zn) antimicrobials is still a great challenge (Abendrot and Kalinowska 2018 ). Previous in vivo studies demonstrated many beneficial impacts of supplemental Zn (organic or inorganic) on different physiological and immunological functions, positive impact on animal health and performance, and some of them deal with the effect on the gut bacterial composition (Bujňáková et al 2023 ), since Zn in appropriate concentration is essential for microorganisms, although conversely, the antimicrobial effect of excess Zn is well-known (Molnar-Nagy et al 2022 ). The most common used inorganic Zn derivatives are Zn(II) sulphates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the search for new zinc (Zn) antimicrobials is still a great challenge (Abendrot and Kalinowska 2018 ). Previous in vivo studies demonstrated many beneficial impacts of supplemental Zn (organic or inorganic) on different physiological and immunological functions, positive impact on animal health and performance, and some of them deal with the effect on the gut bacterial composition (Bujňáková et al 2023 ), since Zn in appropriate concentration is essential for microorganisms, although conversely, the antimicrobial effect of excess Zn is well-known (Molnar-Nagy et al 2022 ). The most common used inorganic Zn derivatives are Zn(II) sulphates.…”
Section: Introductionmentioning
confidence: 99%